NUCLEAR CYTOLOGY OF CALLUS DERIVED FROM SEEDS AS EXPLANT IN CARTHAMUS TINCTORIUS L. - SRIKANTI KUMARI,; RAMESH KUMAR PANDEY, (The Bioscan, 2010)
Fresh seeds were used as sources of explant from Carthamus tinctorius plants and those of their derived calli were analyzed for chromosomal variation. Although the callus was obtained from different combinations and concentrations of phytohormones but the best callus was induced in different concentrations of 2, 4 – D. It was maintained for five subcultures and cytology was done after every subculture. The majority of the calli (75%) cells showed normal mitosis, however, some cells with mitotic abnormalities were also found.